2015
DOI: 10.1016/j.jcmg.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Carotid FDG Uptake Improves Prediction of Future Cardiovascular Events in Asymptomatic Individuals

Abstract: High carotid FDG uptake predicts cardiovascular events independent of traditional risk factors and CIMT in asymptomatic adults and may add to risk stratification beyond the FRS and CIMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
29
0
5
Order By: Relevance
“…34,35 In addition, carotid artery TBR has been shown to strongly predict subsequent cardiovascular disease in patients with no previous history of cardiovascular disease independent of traditional risk factors. 36 Moreover, when we examined which variables including carotid artery SUV, venous blood SUV, and TBR value were independently associated with %FMD, TBR value was the strongest correlate of decreased %FMD (β=−2.506; P=0.002). Carotid artery SUV (β=0.295; P<0.001), %FMD (β=0.017; P<0.001), and prevalence of coronary artery disease (β=−0.125; P=0.016) were independently correlated with blood pool SUV.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 In addition, carotid artery TBR has been shown to strongly predict subsequent cardiovascular disease in patients with no previous history of cardiovascular disease independent of traditional risk factors. 36 Moreover, when we examined which variables including carotid artery SUV, venous blood SUV, and TBR value were independently associated with %FMD, TBR value was the strongest correlate of decreased %FMD (β=−2.506; P=0.002). Carotid artery SUV (β=0.295; P<0.001), %FMD (β=0.017; P<0.001), and prevalence of coronary artery disease (β=−0.125; P=0.016) were independently correlated with blood pool SUV.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…32,33 Furthermore, TBR calculated as arterial standardized uptake value (SUV) score divided by venous blood SUV is generally used as an index of a quantitative parameter of vascular inflammation. 23,[32][33][34][35][36] Indeed, Tawakol et al 23 reported that TBR values in the carotid arteries were closely correlated with accumulation of CD68-positive macrophages in the corresponding histological sections of patients with severe carotid stenoses (r=0.85; P<0.001). Carotid TBR values were higher in patients with high-risk morphological features of atherosclerotic plaques, such as echolucent plaques, positive remodeling, luminal irregularity, and low attenuation in computed tomographic, than those without.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Moon et al [5] found a correlation of carotid FDG uptake and FRS, but not of carotid intima/media ratio, as a predictor of events during an average follow-up of 4.2 years. Similarly, Hetterich et al [6] found a correlation of FDG vascular uptake with traditional risk factors.…”
Section: Microcalcification (mentioning
confidence: 99%
“…For example, MRI after the administration of recombinant HDL particles containing gadolinium 149 or ultra-small particles of iron oxide 150 can provide information about macrophage infiltration in plaque, or with microparticles of iron oxide targeting VCAM1 can provide information about endothelial activation -a critical step in atherosclerosis pathogenesis 103 . The use of 18 FDG-PET in combination with MRI can also improve characterization of plaque 'activity', with uptake indicating macrophage activity 151 ; high carotid FDG uptake is an independent predictor of cardiovascular events in asymptomatic patients 152 . The use of other tracers, such as 18 F-NaF, have also been used to identify microcalcification in the identification and localization of high-risk coronary plaques 153 .…”
Section: Molecular Techniques-mentioning
confidence: 99%